Réponses

2014-03-02T14:35:15+01:00
A= 2(x-3) -(2x+1) +3(5-2x) A= 2x-6 -2x-1 +15-6x A= -4x +8 pour x= 0 A=2(0-3)-(2*0+1)+3(5-2*0) A=0-6-0-1+15-0 A=8 pour x=1 A= 2(1-3)-(2*1+1) +3(5)2*1) A=2-6-2-1+15-6 A=-4-3+15-6 A=-7-6+15 A=-13+15 A=+2 Voila j'espère t'avoir aider.
Derien mais il ni a pas de B ? Comme tu las écrit
a= 2(x-3)-(2x+1)+3(5-2x) POUR [tex] \frac{2}{3} [/tex]
Ah bas pour celle la si tu veux :
sa fais sa :
2(2/3 -3) - (2*2/3+1) + 3(5-2*2/3) = (4/3-6) - (4/3+1) + (15 - 12/3) = (4/3-18/3) - (4/3+3/3) + (45/3-12/3) = -14/3 -7/3 + 33/3 = -21/3 + 33/3 = 12/3